Knowledge Levels of Pre-Marital Couples on Stunting Prevention after the Exposure to an E-Module - Romadhoni, Intan; Kurniawati, Erna Yovi; Iriyani, Elfrida (Agribiohealth (Journal of Agriculture, Biology & Health Sciences), 2024)
Stunting is a significant public health issue affecting children under five, commonly resulting from chronic malnutrition and infections during early childhood. This descriptive study was conducted in 2023 at the Marriage Registration Office (KUA) in Imogiri sub-district, an area selected due to high stunting rates in the villages of Jatimulyo, Muntuk, and Karangtengah. The study aimed to assess the knowledge levels of pre-marital couples regarding stunting prevention after exposure to a digital e-module. Using purposive sampling, 15 respondents were selected based on their willingness to participate and ability to complete the module. The e-module was chosen for its accessibility, scalability, and interactive features, making it suitable for reaching a broad audience and accommodating varied learning paces. Pretest and posttest assessments demonstrated that the e-module effectively improved participants’ knowledge, as shown by a notable increase in average posttest scores. These results highlight the potential benefits of incorporating digital health education into pre-marital counseling programs to raise awareness on stunting prevention. Future efforts should consider adapting this module to diverse cultural contexts and evaluating its role within a broader national health strategy to support child health outcomes in Indonesia.